2003
DOI: 10.1007/s00421-002-0756-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin C supplementation on oxidative and salivary IgA changes following an ultramarathon

Abstract: This randomized study measured the influence of vitamin C ( N=15) compared to placebo ( N=13) supplementation on oxidative and salivary immunoglobulin A (sIgA) changes in runners competing in an ultramarathon race. Seven days prior to the race, subjects ingested in randomized, double-blind fashion three 500-mg tablets of vitamin C or placebo each day. On race day, blood and saliva samples were collected 1 h pre-race, after 32 km of running, and then again immediately post-race. During the race, runners receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
21

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 51 publications
4
29
0
21
Order By: Relevance
“…From the seven trials (Nehlsen-Cannarella et al, 1997; Henson et al, 1998Henson et al, , 1999Rohde et al, 1998;Koch et al, 2001;Krzywkowski et al, 2001a) that assessed the lymphocyte proliferative response, only one (Koch et al, 2001) found a less depressed proliferative response when CHO was used. None of the interventions had any effect on salivary IgA in the five trials in which IgA was one of the outcomes (Mero, 1997;Bishop et al, 1999;Krzywkowski et al, 2001b;Nieman et al, 2003;Palmer et al, 2003).…”
Section: Nutrition and Exercise-induced Immunodepressionmentioning
confidence: 88%
“…From the seven trials (Nehlsen-Cannarella et al, 1997; Henson et al, 1998Henson et al, , 1999Rohde et al, 1998;Koch et al, 2001;Krzywkowski et al, 2001a) that assessed the lymphocyte proliferative response, only one (Koch et al, 2001) found a less depressed proliferative response when CHO was used. None of the interventions had any effect on salivary IgA in the five trials in which IgA was one of the outcomes (Mero, 1997;Bishop et al, 1999;Krzywkowski et al, 2001b;Nieman et al, 2003;Palmer et al, 2003).…”
Section: Nutrition and Exercise-induced Immunodepressionmentioning
confidence: 88%
“…It was shown that plasma vitamin C is lowered in chronic or acute oxidant states [24,30,36]. Only few studies have monitored concentrations and vitamin C supplementation in saliva [17,39,42,43,45,47]. Requirement for vitamin C is in humans satisfied by the ordinary diet [29].…”
Section: Effect Of Vitamin Cmentioning
confidence: 99%
“…Therefore, there was not influence of the supplementation over the TBARS concentrations. Palmer et al (41) have observed that supplementation with 1.500 mg of vitamin C/day for seven days before and during an ultramarathon did not attenuate the oxidative stress after the event. The inefficiency of the vitamin C supplementation over the LP was attributed to the fact that this vitamin is located in aqueous compartments, being less efficient in neutralizing lipophilic radicals, not directly reacting with radicals generated in the lipidic membrane.…”
Section: Vitamin Cmentioning
confidence: 99%